PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HIGHER ORDER THINGKING SKILLS (HOTS) MATEMATIS SISWA - Hodiyanto Hodiyanto (Universitas PGRI Adi Buana Surabaya, 2018)
The general objective of this study was to determine the effect of the Problem Based Learning model on the students' Higher Order Thingking Skills (HOTS) in the material of system of two-variable linear equations in class X of SMA Negeri 9 Pontianak. The specific objectives are (1) to find out the mathematical Higher Order Thingking Skills (HOTS) before and after applied Problem Based Learning in the material of system of two variable linear equations in class X of SMA Negeri 9 Pontianak. (2) to determine the effect and influence of the Problem Based Learning model on students' Higher Order Thingking Skills (HOTS) in the material of system of two-variable linear equations in class X of SMA Negeri 9 Pontianak. The method used in this study is an experiment, with a Pre-Experimental Design research form. The design in this study is One Group Pretest-Posttest Design, which uses only one sample group given the initial test and final test after being given treatment. Based on the results of data analysis conducted on the findings in the field, the results of this study indicate that there is an influence of the Problem Based Learning model on mathematical students' Higher Order Thingking Skills (HOTS) in the two-variable linear equation system material in class X Pontianak State High School 9. Keywords: Problem Based Learning, Higher Order Thingking Skills, experiment.